MARVELL'S WATERY MAZE: DIGRESSION AND DISCOVERY AT NUN APPLETON. - Cotterill, Anne (ELH)
Focuses on the containment of the country house as depicted in the poem 'Upon Appleton House,' in England. Increase of the theoretical sophistication and narrative disjunction; Implication of historical and psychoanalytical complexity; Relationship between transgression and moral deviation.